Mobile Web-Based Follow-up for Postoperative ACL Reconstruction: A Single-Center Experience. Issue 12 (21st November 2017) - Higgins, James; Semple, John; Murnaghan, Lucas; Sharpe, Sarah; Theodoropoulos, John
Background: The initial 6 weeks after surgery has been identified as an area for improvement in patient care. During this period, the persistence of symptoms that go unchecked can lead to unscheduled emergency room and clinic visits, calls to surgeons' offices, and readmissions. Purpose: To analyze postoperative data from a previous study examining postoperative outcomes in 2 patient populations following breast reconstruction and anterior cruciate ligament (ACL) reconstruction with use of a patient-centered mobile application. Here, the authors establish whether this method of follow-up can provide useful insight specific to the orthopaedic patient population, and they determine whether the mobile platform has the potential to modify their postoperative treatment. In addition, the authors examine its utility for orthopaedic physicians and patients. Study Design: Case series; Level of evidence, 4. Methods: Eligible patients undergoing ACL reconstruction from 2 surgeons were consecutively recruited to use a mobile smartphone application that allowed physicians to monitor their recovery at home. Data from 32 patients were collected via the application and analyzed to evaluate recovery trends during the first 6 postoperative weeks. Following completion of the study, patients and physicians were interviewed on their experience. Results: Data collected from each question in the mobile application provided insightful trends on daily real-time indicators of postoperative recovery. The application identified 1 patient who required in-person reassessment to rule out a possible infection, following surgeon review of an uploaded image. It was estimated that the majority of patients could have avoided follow-up at 2 and 6 weeks, owing to the application's efficacy. Participants described their satisfaction with the device as excellent (43%), good (40%), fair (10%), and poor (7%), and 94% (n = 30) of patients reported that they would respond to questions using a similar application in the future. Both physicians rated their experience as positive and identified useful traits in the web portal. Conclusion: This system can accurately assess patient recovery; it has the potential to change how postoperative orthopaedic patients are followed, and it is well received by patients and physicians. Recognition of the study's limitations and employment of user feedback to improve the current application are essential before a formal randomized controlled trial is conducted.